MARKETING STRATEGY ANALYSIS OF RECYCLED PRODUCTS IN IMPROVING INDEPENDENT GRADUATION OF HOPE FAMILY PROGRAM GROUP - Deden Komar Priatna (Sosiohumaniora, 2022)
Even though it is supported by the Smart City label, as the capital city of West Java Province, Bandung is still having trouble handling waste. The plan to use incinerator technology at the Sarimukti landfill has never been built because it is considered a threat to the environment and public health. Furthermore, biodigester technology from Japan was initiated, but it did not materialize. As a result, waste becomes an unresolved problem. Therefore, according to Law no. 18 of 2008 concerning Waste Management, the paradigm of waste management must be changed from collect-transport-dispose to reduction at source and recycling through the 3R principle (reduce, reuse, recycle). “Pasigaran Handmade and Crafts” was established on July 16, 2019, having its address at Pasigaran Village, Citeureup Village, Dayeuhkolot District, Bandung Regency, West Java Province. This business was founded on the anxiety of companions because more and more poor people need government assistance but cannot be covered by the government budget, in addition to the abundance of paper waste that is no longer used so that the idea of turning newsprint into a variety of recycled products such as wall clocks, bags was born. , tea sets and various containers. The essence of planning is how to determine various programs and activities aimed at gradually achieving long-term goals. Therefore, the preparation of programs and activities must be based on organizational goals, both short term (0-2 years) and long term (2-5 years). Performance measures are carried out by setting indicators of success, both short term and long term